Silver-Russell patients showing a broad range of ICR1 and ICR2 hypomethylation in different tissues - Begemann, M.; Spengler, S.; Kanber, D.; Haake, A.; Baudis, M.; Leisten, I.; Binder, G.; Markus, S.; Rupprecht, T.; Segerer, H.; Fricke-Otto, S.; Mühlenberg, R.; et al. (Clinical Genetics, 2011)
In all known congenital imprinting disorders an association with aberrant methylation or mutations at specific loci was well established. However, several patients with transient neonatal diabetes mellitus (TNDM), Silver-Russell syndrome (SRS) and Beckwith-Wiedemann syndrome (BWS) exhibiting multilocus hypomethylation (MLH) have meanwhile been described. Whereas TNDM patients with MLH show clinical symptoms different from carriers with isolated 6q24 aberrations, MLH carriers diagnosed as BWS or SRS present only the syndrome-specific features. Interestingly, SRS and BWS patients with nearly identical MLH patterns in leukocytes have been identified. We now report on the molecular findings in DNA in three SRS patients with hypomethylation of both 11p15 imprinted control regions (ICRs) in leukocytes. One patient was a monozygotic (MZ) twin, another was a triplet. While the hypomethylation affected both oppositely imprinted 11p15 ICRs in leukocytes, in buccal swab DNA only the ICR1 hypomethylation was visible in two of our patients. In the non-affected MZ twin of one of these patients, aberrant methylation was also present in leukocytes but neither in buccal swab DNA nor in skin fibroblasts. Despite mutation screening of several factors involved in establishment and maintenance of methylation marks including ZFP57, MBD3, DNMT1 and DNMT3L the molecular clue for the ICR1/ICR2 hypomethylation in our patients remained unclear. Furthermore, the reason for the development of the specific SRS phenotype is not obvious. In conclusion, our data reflect the broad range of epimutations in SRS and illustrate that an extensive molecular and clinical characterization of patients is necessary. © 2010 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2025-03-05